An evaluation of the cataloging and classification practices among LibraryLink member-institutions in Metro Manila Angelina C. Mallanao ; Nathalie N. Dela Torre, adviser ; Rosalie B. Faderon, reader. - Mallanao, Angelina C.; Dela Torre, Nathalie N.; Faderon, Rosalie B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
This study was conducted to assess the degree of adherence or deviation of eleven member-institutions of LibraryLink from the standard rules to know the reasons behind such deviations or modifications and to verify the completeness of information found in LibraryLink records. It aims to provide possible ways on how an important facet of cataloging work can be improved in a network.
The descriptive research method was used; Analysis of extracted LibraryLink records common to at least five respondent libraries as well as a survey was also used to gather data. Tables showing percentage and frequency were used in the analysis and interpretation a. The following are the major findings of the study: 1) Eight of the twenty-five catalogers hold master's degree while the rest are undergraduate studies in the same field. 2) Tasks related to cataloging and classification is being done by one person or one group while three of the respondent libraries require their catalogers to to other task outside cataloging. 3) Both original cataloging and copy cataloging is being performed by most respondent libraries. 4) Seven respondent libraries use AACR2 while the rest use AACR2R 5) Many respondent libraries deviate in one or more areas in the rules for descriptive cataloging, as well as in choosing main access point and form headings. 6) In assigning subject headings, eight of the respondent libraries use LCSH while the others use Sears List of Subject Headings. Majority of the respondent libraries use Filipiniana List of Subject Headings secondarily to LCSH. 7) Seven respondent libraries use various editions of LCC while the rest either use only DDC or both. Almost half of the respondent libraries do some degree of modifications from the basic subject heading and classification tools and processes due to limitation of the authorized classification scheme to cover a much comprehensive cataloging system on Filipiniana materials. As such they have resorted to make their own schedule of their classification scheme exclusively used in-house. 8) As to the efficiency of LibraryLink records, it shows that 31.5 have inconsistent transcription which means that there are about 1,608 entries found to be missing in LibraryLink yet available in library catalogs of the member-institutions.
Based on the findings of the study, it is recommended that the following should be undertaken to achieve the network's goal in becoming a surrogate to local catalogs of Filipiniana collection. 1) That the steering committee must be strengthened to evaluate current issues in the union catalog system and draft recommendations for further improvements. 2) Efforts should be made towards verifying the completeness and accuracy of submitted records before uploading it to the web. 3) LibraryLink should spearhead in implementing new trends in cataloging such as Resource Description and Access (RDA) to member-institutions as well as moving its database to MARC compliant if not at least to an XML format to ensure interoperability.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Cataloging; Classification; Library cooperation -- Philippines -- Manila Metropolitan Area